Randomized controlled trial of pregabalin for analgesia after surgical treatment of intervertebral disc disease in dogs. Issue 5 (23rd April 2020) - Schmierer, Philipp A.; Tünsmeyer, Julia; Tipold, Andrea; Hartnack‐Wilhelm, Sonja; Lesczuk, Piotr; Kästner, Sabine B. R.
Abstract: Objective: To assess the effect of perioperative pregabalin on pain behavior in dogs after intervertebral disc surgery. Study design: Prospective, randomized, controlled clinical trial with a blinded observer. Animals: Forty‐six client‐owned dogs undergoing intervertebral disc surgery. Methods: Dogs were randomly assigned to two groups, with the placebo group receiving opioids alone and the pregabalin group receiving opioids plus pregabalin. Opioid analgesia consisted of 0.6 mg/kg l‐methadone given intravenously at anesthetic induction, followed by 0.2 mg/kg given at 8, 16, and 24 hours after extubation and fentanyl patches applied at the end of surgery. Pregabalin was given orally (4 mg/kg) 1 hour before anesthesia, followed by postoperative treatment three times per day (4 mg/kg) for 5 days. The outcome measures were the treatment‐group differences in peri‐incisional mechanical sensitivity and Glasgow Composite Measure Pain Scale (CMPS‐SF) assessed during the first 5 postoperative days. Pregabalin serum concentrations were measured after 24, 72, and 120 hours. Results: Pregabalin reduced pain levels in the treatment group by a mean of 2.5 CMPS‐SF units (95% confidence interval [CI] = −3.19 to −1.83, P < .001) compared with the control group during the study period. Pregabalin increased the mechanical nociceptive threshold by a mean of 6.89 N per day (95% CI = 1.87‐11.92, P < .001) and of 7.52 N per day (95% CI = 2.29‐12.77, P < .001) during the study period, depending on location. Mean levels of serum pregabalin were 5.1, 4.71, and 3.68 μg/mL at 24, 72, and 120 hours postoperatively, respectively. Conclusion: Postoperative signs of pain after surgical treatment of intervertebral disc herniation (IVDH) were reduced when dogs received perioperative pregabalin rather than opioids alone. Clinical significance: Perioperative pregabalin reduces postoperative pain after surgical treatment of IVDH.